The Influence of Work Environment And Teamwork on Employee Performance in The General Administration, Finance, Infrastructure And Human Resources in Muhammadiyah University of Makassar - Sitti Hajar M. Arsyad; Ahmad AC; Edi Jusriadi (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to determine, analyze, and describe the effect of the work environment and teamwork on employee performance at the General Administration, Finance, Infrastructure, and Human Resources Bureau of Muhammadiyah University Makassar, using multiple linear regression analysis. This is a quantitative study using questionnaires as a source of data collection. This study used 73 respondents from The General Administration, Finance, Facilities and Human Resources Office at Universitas Muhammadiyah Makassar. The results showed that the work environment had a positive and significant effect on employee performance at the General Administration, Finance, Facilities and Human Resources Office at Muhammadiyah University Makassar, with a coefficient value of 0.061 and significance of 0.048, and that teamwork had a positive and significant effect on employee performance in the General Administration, Finance, Facilities and Human Resources Office at Muhammadiyah University Makassar, with a coefficient value of 0.360 and significance of 0.000. Thus, the work environment not only affects employee satisfaction and well-being, but also contributes to improving overall employee performance and teamwork supported by guidance on capabilities, effective communication, shared responsibility, and a spirit of mutual contribution, which has been proven to improve employee performance by realizing the objectives to be achieved by the General Administration, Finance, Facilities and Human Resources Office at Universitas Muhammadiyah Makassar